2021
DOI: 10.1051/0004-6361/202040093
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies of carbon isotopic fractionation in reactions of C with C2: dynamics, kinetics, and isotopologue equilibria

Abstract: Context. Our current understanding of interstellar carbon fractionation hinges on the interpretation of astrochemical kinetic models. Yet, the various reactions included carry large uncertainties in their (estimated) rate coefficients, notably those involving C with C2. Aims. We aim to supply theoretical thermal rate coefficients as a function of the temperature for the gas-phase isotope-exchange reactions 13C+12C2(X1Σg+,a3Πu)⇌13C12C(X1Σg+,a3Πu)+12C and 13C+13C12C(X1Σg+,a3Πu)⇌13C2(X1Σg+,a3Πu)+12C. Methods. By … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…For example for our Reaction (5) in the forward direction ( 13 C + C 2 → 12 C + 13 CC), we obtain a rate coefficient of 2.89 × 10 −10 cm −3 at 10 K, whereas the fit of Rocha & Linnartz (2021) gives 1.52 × 10 −11 cm −3 -though it is to be noted that the rate coefficients of Rocha & Linnartz (2021) were calculated for higher temperatures (upward of 25 K) than we consider here (10 K in most simulations). We tested the effect of switching to the Rocha & Linnartz (2021) rate coefficients for their reactions (2) and (3) (with the C 2 variants in the X 1 Σ + g state) by running new variants of simulations S1, S2, and S3 with the rate coefficients of the reactions in question switched to the Rocha & Linnartz (2021) values. We found that the effects on the simulation results are highly dependent on the physical conditions.…”
Section: Effect Of H 2 Oprmentioning
confidence: 85%
See 1 more Smart Citation
“…For example for our Reaction (5) in the forward direction ( 13 C + C 2 → 12 C + 13 CC), we obtain a rate coefficient of 2.89 × 10 −10 cm −3 at 10 K, whereas the fit of Rocha & Linnartz (2021) gives 1.52 × 10 −11 cm −3 -though it is to be noted that the rate coefficients of Rocha & Linnartz (2021) were calculated for higher temperatures (upward of 25 K) than we consider here (10 K in most simulations). We tested the effect of switching to the Rocha & Linnartz (2021) rate coefficients for their reactions (2) and (3) (with the C 2 variants in the X 1 Σ + g state) by running new variants of simulations S1, S2, and S3 with the rate coefficients of the reactions in question switched to the Rocha & Linnartz (2021) values. We found that the effects on the simulation results are highly dependent on the physical conditions.…”
Section: Effect Of H 2 Oprmentioning
confidence: 85%
“…In model S3, the rate coefficients of these reactions play only a very minor role, but in the highdensity and low-temperature environment of model S1 we obtain variations of up to an order of magnitude in the 12 C/ 13 C ratios of C 2 (and typically a factor of a few for other ratios) depending on the choice of the rate coefficients. The reason why the Rocha & Linnartz (2021) coefficients are so much lower than ours, or those of Loison et al (2020), is unknown at present and hence we have not included their rate coefficients in the bulk of the analysis presented here. However, these tests highlight that constraining the rate coefficients of critical reactions is of great importance for the predictions of chemical models, and further experimental and theoretical work on this is called for.…”
Section: Effect Of H 2 Oprmentioning
confidence: 88%